Is the Oral Microbiome Important in HIV-Associated Inflammation? - Jennifer A. Fulcher (American Society for Microbiology, 2020)
ABSTRACT Alterations in the gut microbiome during HIV infection have been implicated in chronic inflammation, but the role of the oral microbiome in this process is less clear. The article by M. K. Annavajhala, S. D. Khan, S. B. Sullivan, J. Shah, et al. (mSphere 5:e00798-19, 2020, https://doi.org/10.1128/mSphere.00798-19) investigated the relationship between oral and gut microbiome diversity and immune activation in patients with HIV on antiretroviral therapy. In this study, oral microbiome diversity was inversely associated with inflammatory markers such as soluble CD14 (sCD14), but surprisingly similar associations were not seen with gut microbiome diversity. Oral microbiome diversity was also associated with periodontitis in these patients. This study highlights the importance of continuing multisite examinations in studying the gastrointestinal tract microbiome and also stimulates important directions for future research defining the role of the oral-gut axis in HIV-associated inflammation.